Adjustment of growth parameters for the major body components of pullets - Silva, Edney; Sakomura, Nilva; Dorigam, Juliano Cesar; Malheiros, Euclides; Peruzzi, Nelson (Revista Ciência Agronômica, 2016)
The purpose of this research was analyze the fit of Gompertz function with or without fixing some of the parameters to describe body growth and major bodily chemical constituents of growing pullets. Weekly, data of body weight and chemical components of body free of feathers and feathers were collected from 1,200 chicks of four laying strains (Hisex Brown, Hisex White, Hy Line Brown and Hy Line White W36) until 18 weeks of age. The variables were subjected to two adjustments fixing, or not, some parameters of Gompertz function. The allometric model parameters were calculated for the chemical components. The lipid and protein composition of the body free of feathers were the components with the biggest change in the last weeks. Moreover, the chemical composition of the feather showed small variation. The parameters of the Gompertz function assumed values according to the employed adjustment, especially for protein and fat of the body free of feathers carcass. The adjustment of the Gompertz function by fixing the two parameters allowed coherence and biological significance. The allometric coefficients indicate that as the protein weight increased, the proportion of fat increased and the proportion of water and ashes in the body decreased. The fit of the model allows setting the parameters with consistency and biological significance without losing accuracy in the estimates.